Risk-return trade-off for European stock markets - Aslanidis, Nektarios; Christiansen, Charlotte; Savva, Christos S. (My University, 2016)
This paper adopts factor models with macro-finance predictors to test the intertemporal risk-return relation for 13 European stock markets from 1986 to 2012. We use country specific, euro area, and US macro-finance factors to determine the conditional volatility and conditional return. We find that the risk-return trade-off is generally negative. The Markov switching model documents that there is time-variation in this trade-off that is linked to the state of the economy, but not the business cycles. Quantile regressions show that the risk-return trade-off is stronger at the lowest quantile of the conditional return.
Keywords: European stock markets; Risk-return trade-off; Factor model; Quantile regressions